Faktor Resiko Dispepsia Fungsional pada Mahasiswa Fakultas Kedokteran Universitas Bosowa Angkatan 2019-2021 - Randini, Waode Lidya Viska; Sartika, Suriana Dwi; Rahmadani, Andi Anissa (Bosowa Medical Journal, 2024)
Dyspepsia is a syndrome or a collection of symptoms/complaints consisting of pain or discomfort in the pit of the stomach, bloating, nausea, vomiting, belching, feeling full quickly, stomach feeling full/full. There are several risk factors for functional dyspepsia. Functional dyspepsia occurs due to various reasons, most commonly due to increased stomach acid production or decreased resistance of the stomach wall to external influences. The purpose of this study was to determine the risk factors for functional dyspepsia (1) diet (2) stress (3) history of alcohol consumption (4) history of consumption of NSAIDs. This research was conducted on 100 people with functional dyspepsia syndrome at the Faculty of Medicine, University of Bosowa. This study used an analytic method with a cross-sectional study design using primary data in the form of interviews with functional dyspepsia sufferers in students of the Faculty of Medicine, University of Bosowa Class of 2019-2021. Data analysis was processed using SPSS software. The results of this study indicate the risk factors for functional dyspepsia in students of the Faculty of Medicine, University of Bosowa Batch 2019-2021, namely: (1) There was no significant relationship between diet and functional dyspepsia, (2) There was a significant relationship between stress and functional dyspepsia, (3) ) There was no relationship between history of alcohol consumption and functional dyspepsia, (4) There was no significant relationship between history of consumption of NSAIDs and functional dyspepsia. The conclusion of the study is that stress is a risk factor for functional dyspepsia in students of the Faculty of Medicine, University of Bosowa.